Crystal Growth of IRMOF-3 (Isoreticular Metal-Organic Frameworks-3) Synthesized using Solvothermal Method - Pemta Tia Deka; Ratna Ediati; Didik Prasetyoko (Institut Teknologi Sepuluh Nopember, 2014)
IRMOF-3 crystals have been synthesized using solvothermal method by reacting zinc nitrate hexahydrate with 2-amino-1,4-benzenedicarboxylic acid in N'N-dimethylformamide ( DMF ) at 100 °C for 18, 24, 48, 72, 120 and 144 h to observe crystal growth . The obtained crystals were characterized using X - ray Diffraction ( XRD ) , SEM ( Scanning Electron Microscopy ) and Scanning Electron Microscopy - Energy Dispersive X-ray ( SEM - EDX ). Diffractograms of crystals synthesized at heating times of 24 and 48 hours showed major peaks at 2θ of 6.8; 9.6 and 13.7, which are the characteristic peaks of an IRMOF-3 crystal. The size of IRMOF-3 crystals observed using SEM increased with the increase in heating time up to 48 h, then decreased at heating times of 72, 120 and 144 h. The largest IRMOF-3 crystal is of cube shape with a particle size of 500 µm. The weight of the resulting crystals increased with the increase in heating time, then remained constant after 72 h.